Using the BODY‐Q to develop a prospective cohort of patients undergoing bariatric and body contouring surgery: A study protocol. Issue 1 (5th December 2022) - Grift, Annewiek; de Vries, Claire; Monpellier, Valerie; Makarawung, Dennis; de Raaff, Christel; Nijland, Leontien; Mink van der Molen, Aebele; Wiezer, Rene; van Wagensveld, Bart; van Veen, Ruben; de Castro, Steve; Florisson, Joyce; et al.
Summary: The BODY‐Q is a patient‐reported outcome measure designed to measure health‐related quality of life, satisfaction with appearance and experience with healthcare in patients with obesity who undergo bariatric surgery and/or body contouring surgery after massive weight loss. The aim of this study is to collect long term PRO‐data from patients living with obesity undergoing bariatric surgery, comparing patient undergoing or not undergoing body contouring surgery. This study will be a multicentre, prospective longitudinal cohort study with participation of three bariatric medical centres in the Netherlands. The BODY‐Q will be used to measure the satisfaction with appearance and HRQL. Patients undergoing bariatric surgery, age >18 years and <65 years and who are able to read and understand Dutch can be included. All bariatric procedures are eligible for inclusion. Administration of the questionnaires will be done preoperatively for bariatric and body contouring surgery as well as at 3, 12, 24, 36, 48 and 60 months post‐operatively. Patient‐reported outcomes measurements are becoming more important with the shift to patient‐centred healthcare. The collected longitudinal data can be helpful in determining the effectiveness and value of bariatric and body contouring surgery from the patient's perspective, and can contribute to patient tailored postoperative care.